Pridobivanje govornih virov: Prednosti in pomanjkljivosti različnih pristopov - Bizjak, Andreja (University of Maribor Press, 2025)
Collection of Speech Resources: Advantages and Limitations of Different Approaches. This study systematically examines various approaches to collecting speech resources for Slovenian – from laboratory and field recordings to more contemporary online methods such as GWAPs, Collect4NLP, crowdsourcing, and citizen science. Through a comparative analysis that considers sound quality, cost, scalability, and speech spontaneity, it reveals the advantages, limitations, and implementation challenges of each approach. The work provides practical recommendations for researchers and developers of speech technologies who face the challenges of remote recording. By integrating global trends and international practices with the Slovenian context, it contributes to the development of digital speech resources and the advancement of language technologies for under-resourced languages.